To Internet or Not?: Assessing the Efficacy of Online Police Training - Donavant, Brian W. (American journal of criminal justice, 2009)
The field of police training is undergoing a paradigm shift due to technology, and this study used an andragogical lens to explore various considerations for the implementation of online education (OE) into police training regimens. This comprehensive assessment utilized quantitative and qualitative methods to examine the feasibility of OE for professional development among police officers in Tennessee. The study examined whether the potential performance of police officers in OE is related to various demographic factors and evaluated the perceptions of police regarding online education. Data analyses indicated a statistically significant relationship between potential online learning success and various factors, including formal educational level and previous exposure to OE. The majority of participants in the study said they preferred OE to traditional instruction, felt that OE is an appropriate delivery method for professional development, and believed that the use of OE for delivery of professional development provides increased training opportunities.